Analisis Semiotik Roland Barhtes Pada Lagu dalam Album “Selamat Ulang Tahun” Karya Nadin Amizah - Utari Putri, Alicia; Fathurrahman, Irfai; Hariyadi, Ahmad (Journal Sains and Education, 2024)
This research aims to describe the semiotics of Roland Barthes in Nadin Amaziah's song in Nadin Amizah's album "Selamat Birthday" in his song. This research is included in the semiotic study that focuses on Roland Barthes' theory. The data source of this study uses the lyrics of the song in the album "Selamat Birthday" by Nadin Amizah which contains Rolan Barthes' semiotics. The method used in this study is a qualitative method through an objective approach. The technique used in data collection uses reading, reading and recording techniques. The data in this study uses the lyrics of songs in the album "Selamat Birthday" by Nadin Amizah which contain Rolan Barthes semiotics which will be grouped according to their form, namely connotations, denotations and myths.